Retention and mortality on antiretroviral therapy in sub‐Saharan Africa: collaborative analyses of HIV treatment programmes. Issue 2 (26th February 2018) - Haas, Andreas D; Zaniewski, Elizabeth; Anderegg, Nanina; Ford, Nathan; Fox, Matthew P; Vinikoor, Michael; Dabis, François; Nash, Denis; Sinayobye, Jean d'Amour; Niyongabo, Thêodore; Tanon, Aristophane; Poda, Armel; et al.
Abstract: Introduction: By 2020, 90% of all people diagnosed with HIV should receive long‐term combination antiretroviral therapy (ART). In sub‐Saharan Africa, this target is threatened by loss to follow‐up in ART programmes. The proportion of people retained on ART long‐term cannot be easily determined, because individuals classified as lost to follow‐up, may have self‐transferred to another HIV treatment programme, or may have died. We describe retention on ART in sub‐Saharan Africa, first based on observed data as recorded in the clinic databases, and second adjusted for undocumented deaths and self‐transfers. Methods: We analysed data from HIV‐infected adults and children initiating ART between 2009 and 2014 at a sub‐Saharan African HIV treatment programme participating in the International epidemiology Databases to Evaluate AIDS (IeDEA). We used the Kaplan–Meier method to calculate the cumulative incidence of retention on ART and the Aalen–Johansen method to calculate the cumulative incidences of death, loss to follow‐up, and stopping ART. We used inverse probability weighting to adjust clinic data for undocumented mortality and self‐transfer, based on estimates from a recent systematic review and meta‐analysis. Results: We included 505, 634 patients: 12, 848 (2.5%) from Central Africa, 109, 233 (21.6%) from East Africa, 347, 343 (68.7%) from Southern Africa and 36, 210 (7.2%) from West Africa. In crude analyses of observed clinic data, 52.1% of patients were retained on ART, 41.8% were lost to follow‐up and 6.0% had died 5 years after ART initiation. After accounting for undocumented deaths and self‐transfers, we estimated that 66.6% of patients were retained on ART, 18.8% had stopped ART and 14.7% had died at 5 years. Conclusions: Improving long‐term retention on ART will be crucial to attaining the 90% on ART target. Naïve analyses of HIV cohort studies, which do not account for undocumented mortality and self‐transfer of patients, may severely underestimate both mortality and retention on ART.